Diesel Particulate Matter Exposure Increased HbA1c and Apo-B Level in Blood on Motor Vehicle Testing Officer Cilincing Jakarta, Indonesia - Elisabet Butarbutar, D; Fitri, A; Kurniasari, F; Atmajaya, H; Hikmat Ramdhan, D (KnE Life Sciences, 2019)
Diesel particulate matter both fine and ultrafine particulate contribute to daily personal exposure of workers. Exposure to diesel particulate matter in the short term and long term can cause diabetes and atherosclerosis. These health problems include changes in glucose, HbA1c, lipids, and Apoliprotein-B (Apo-B). This study aimed to analyze the exposure of diesel particulate matter associated with increased HbA1c and Apo-B level in blood. The samples were a mechanical test and administrative officer totaling 33 people and 24 people as a comparison group. The research variables are diesel particulate matter exposure, HbA1c level, Apo-b level, age, body mass index (BMI), length of work, and smoking habit. Measurement of particulate matter exposure used Leland Legacy Pump and Sioutas Cascade Impactor. Calculation of exposure concentration used the gravimetric method. Measurements of HbA1c levels in the blood used HPLC Ion Changes method and for Apo-B, it used Polyethyleneglycol (PEG) enhanced immunoturbidimetric assay. The results were mean of Apo-B level in mechanic test officer is 107.30 and in control groups, it’s 91.17 mg/dL. It showed that Apo-B level in mechanic test officer was higher than Apo-B level in control groups. The HbA1c level in blood had ranged from 4.90 % - 6.80 %. mg/dL. The results showed there was a positive correlation among the personal exposure concentrations of PM10, PM2.5, PM1, PM0.5 and PM0.25 with levels of HbA1c in the blood. In this study, sex, age, and BMI were also an independent factor that could increase the HbA1c level. Furthermore, this study also found that sex, age, smoking habit, and BMI also contributed to increasing Apo-B level in blood. Keywords: Diesel Particulate Matter, HbA1c, Apo-B, Vehicle Testing Officer